First record of Dosima fascicularis (Ellis & Solander, 1786) (Crustacea, Cirripedia) in the Strait of Messina (Central Mediterranean Sea) - Cavallaro, M.; Ammendolia, G.; Battaglia, P. (Zootaxa, 2020)
Four specimens of Dosima fascicularis were collected from the Strait of Messina (Central Mediterranean Basin), representing the first record of the species from this locality, the second from Italian waters, and the most eastern indication of the species in the Mediterranean Sea.